The belt and road initiative ASEAN countries' perspectives - Yang, Yue 1976-; Li, Fujian 1986- (Series on China's belt and road initiative, 2019)
"ASEAN countries play a crucial role in the Belt and Road Initiative (BRI) that was initiated in 2013. A number of priority BRI projects have since been implemented. The implementation of BRI brings new opportunities and challenges to countries in the region, and also to regional integration. In this book, researchers from universities and think-tanks in ASEAN countries study the BRI from the perspective of regional studies. It presents an analysis of responses on BRI of the government and people from individual ASEAN members. The book addresses three areas: First, the strengths and weaknesses of ASEAN countries, and the opportunities and challenges for them in implementing the BRI (a SWOT analysis); second, the impacts of BRI on building the ASEAN community; and third, interactions between BRI and ASEAN-China cooperation